Scaffolds à Base de Derivados da Goma Guar e Quitosana: Potenciais Curativos Tópicos - Oliveira, Matheus Xavier de (2023)
The topical injuries could be traumatic or chronic origin. In both cases, the reparation is promoted by building of an environment aseptic with easily cellular proliferation. For it, one of the branches of tissue engineering, has been designing the development to multifunctional therapeutic tools – the biodressings. Generally speaking, theses matrices display up as film, composites, hydrogel and scaffolds. Among the cited, the scaffolds are feature to been porous platforms that mimic the extracellular matrix native allows exchange gaseous, fluids absorption, nutrients carriage, reepithelization promotion and tissue reconstitution. However, furthermore good structural parameters, the dressings must to impair the infiltration and colonization of microbial invaders responsible by inflammatory response – which slowly the healing process. Observing all these aspects, the current work, aim to synthesis of scaffolds based in oxidized guar gum and N-succinyl chitosan with potential wound dressing application. The guar gum e chitosan are polysaccharides endows with pharmacology actions and of attest biocompatibility, thus their derivatives have to aggregate theses values. Firstly, the guar gum – depolymerized through of acid/ethanol treatment – was oxidized with sodium periodate at the theoretical and molar degree of 20, 35 e 50%. Meanwhile, the chitosan was carboxylated with succinic anhydride, turning on water soluble into wide pH range. The main techniques used to characterize the modified polysaccharides were FT-IR, NMR (1H - 13C) and GPC. Through these species were obtained the hydrogels - via Schiff base formation – which after freeze-drying produced the scaffolds. The formulated gels had the gelling time evaluated by oscillatory rheology and the magnetic bar method, in both the assays, can observed a proportional correlation between the magnitude of content guar gum oxidation and reticulation degree. Already the reticulation degree determined the swelling, porosity e degradation proprieties of the scaffolds - named as: SFD-20, SFD-35 and SFD-50. At last, the porous matrices SFD-20, SFD-35 and SFD-50 had their antibacterial activities assess against to S. aureus, E. coli and S. enterica. By mean of the results, could be ratify suitable inhibitory action of SFD-35 and SFD-50 against to S. aureus, E. coli – which together the other specifications – qualify these how possible instruments for stomatherapy.